Spatial Distribution of Epizootic Manifestations of Plague in Connection with Orographic and Edaphic Factors in the Central Caucasian High-Mountain Natural Focus - V. M. Dubyansky; V. M. Mezentsev; U. M. Ashibokov (Проблемы особо опасных инфекций, 2024)
The aim of this work was to clarify the orographic and edaphic parameters of the spatial distribution of epizootic sites in the Central Caucasian high-mountain natural plague focus for electronic certification within the framework of the State Program “Ensuring chemical and biological safety of the Russian Federation, 2021–2024”, R&D “Electronic certification of natural plague and CHF foci in the south of the Russian Federation”. Materials and methods. Data on the spatial and temporal distribution of epizootic sites were obtained from the archive of the Stavropol Anti-Plague Institute of the Rospotrebnadzor. They include 318 points of detection of plague epizootics between 1984 and 2021 with spatial reference in the form of geographical coordinates. The analysis covered four landscape-epizootiological regions (LER): Verkhne-Kubansky, Kubano-Malkinsky, Malko-Baksansky and Baksan-Chegemsky. The Chegem-Chereksky LER was excluded, since no plague strains have been detected from its territory. Edaphic and orographic factors were obtained from the web-sites https://www.fao.org/ (soil data, including names), https://neo.gsfc.nasa.gov/, https://dwtkns.com/srtm30m/ (digital relief model) and from the archive of the Stavropol Anti-Plague Institute of the Rospotrebnadzor. Results and discussion. The epizootic sites have a pronounced confinement to altitudes from 2000 to 2711 meters above sea level. In the mountain-steppe belt, epizootic areas are more often found on the slopes of the North-North-East – South exposures, in the alpine and subalpine belts – the North-North-West exposure. The favorable level of landscape illumination is medium, closer to high; relatively flat or not heavily dissected areas, with soils: dystric and mollic leptosols and dystric cambisols predominate. Epizootic sites are absent on eutric cambisols, although this may be a random phenomenon.